The Wandering Ethnographer: Researching and Representing the City through Everyday Encounters - Moretti, Cristina (Anthropologica, 2022)
Drawing on fieldwork I conducted in Milan, Italy, in 2004-05 and in 2009, this paper is an open invitation to create experimental forms of ethnographic representation that could become part of the unfinished production of the everyday in urban locales. To this end, I reflect on several fieldwork encoun- ters - Milanese people's commentaries, everyday incidents, as well as local cultural and activists' projects - that can provide a helpful model for such a practice. I argue that these varied inter- ventions offer insight into complex social processes and dis- junctures in contemporary Milan because they are small, quo- tidian, and temporary, and because they can easily travel through the urban terrain. Learning from these encounters, I propose that we, too, can produce stories and objects that speak by circulating: ethnographic interventions that use public space, activate affect and become companions to people's embodied journeys in city spaces.